Experiment of Industrial Waste Absorption using Activated Carbon from Coal of Tanjung Tabalong, South Kalimantan - Gani, M. Ulum; Widodo, Widodo (Indonesian Journal on Geoscience, 2011)
DOI:Â 10.17014/ijog.v6i4.130Activated carbon made from Tanjung Tabalong coal was investigated its absorption capability to organic and inorganic elements in industrial waste. Coal was carbonized at low temperature of 600C to produce semicoke, and then was activated at temperature of 700C with activation time of 120 minutes with water steam flow. The absorption capability of activated carbon to chemical oxygen demand (COD) was performed using 2.5 and 9.0 g activated carbon for 250 ml and 300 ml COD waste respectively. The agitation time of each experiment were 30, 60, and 90 minutes. Atomic absorption spectrophotometer (AAS) was used to analyze the COD waste. The result shows that 2.5 g activated carbon could absorb COD waste ranging from 6.9-67.5 %, while the utilization of 9 g could absorb COD waste ranging from 88.9 - 100 %. The more activated carbon and the longer time of agitation used in this experiment, the more the absorption of COD waste.